Evaluasi Penerimaan Teknologi Mobile Internet pada Dosen di Politeknik Negeri Sriwijaya - Irma Salamah; Desi Riama Manalu (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2018)
The use of mobile internet technology in the field of education has been widely used. In college the use of Mobile Internet Technology has a significant influence on the performance of lecturers both in the process of learning and teaching. Research on Sriwijaya State Polytechnic Lecturer aims to evaluate and analyze the factors of acceptance of mobile internet technology to lecturer performance. The survey was conducted on 78 Sriwijaya State Polytechnic lecturers in all departments. The study used the model of acceptance of Mobile Internet Technology with Technology Acceptance Models (TAM) method. Factors analyzed were perceptions of ease of use, perception of utility, social factors, work relevance, perceptions of pleasure towards intentions in the use and use of actual systems. The results showed that the perception factor of usability, job relevance and pleasure perception affect the lecturer's intention to use mobile internet technology. The results also show that the perception of convenience and social factors have no effect on the intention to use mobile internet technology, it is because lecturers are difficult to become proficient in using today's highly sophisticated and ever-growing technology.Keywords— Technology Mobile Internet, TAM, Lecture Performance